Dealing With Radicalised Youth Offenders: The Development and Implementation of a Youth-Specific Framework - Barracosa, Steven; March, James (Frontiers in Psychiatry, 2022)
In 2018 in the Australian State of New South Wales, a specialist Countering Violent Extremism Unit was established in the youth criminal justice system. This was in response to a number of youth below age 18 who have been charged for terrorism offences and involved in violent extremists acts. This youth-specific framework was the first of its kind in Australia. It was designed to provide multidisciplinary practitioner-based approaches for the early-identification, diversion, and disengagement of at-risk and radicalised youth offenders. This paper will explore the experiences and lessons learned by the Youth Justice New South Wales Countering Violent Extremism Unit. It will discuss the relevance of youth radicalisation within Australia’s evolving national security climate. This includes emerging trends in relation to youth radicalisation to varied violent extremist ideologies. This paper will explore the specialist approach adopted for preventing and countering violent extremism through the identification, assessment, and case management of at-risk and radicalised youth offenders. The Youth Justice New South Wales experience indicates that youth criminal justice settings can be designed to tackle the challenges posed by at-risk and radicalised youth. The practitioner experience canvassed in this paper highlights that a pluralistic and non-punitive approach to supervision, client-focused assessment and case management processes, and widespread resourcing of multidisciplinary practitioners and programs can be used to account for developmental vulnerabilities and violent extremism risk factors amongst youth. These approaches should be supplemented by youth-specific countering violent extremism practitioner expertise, and a range of violent extremism case management and risk assessment measures.